Sleep Disorders in Post Stroke Patients : A Literature Review - Putri, Radiah Meilani; T., Rizqy Agung Fatahillah; Lovely, Anjela Fatma; Faqih, Fauzan; Purba G., Andrew Deardo; Fildzani, Qashrina Vania; Rakadi P., Rifky Sandya (Jurnal Biologi Tropis, 2024)
Stroke as a neurological disease caused by vascular injury to the central nervous system, is a leading cause of death and disability worldwide. The impact of a stroke is not only felt at the time of the incident but also post-stroke, particularly in the form of sleep disturbances experienced by 20-78% of patients. This review aims to delve into various aspects related to post-stroke sleep disorders, including definition, etiology, epidemiology, physiology, pathophysiology, management, and impact. These sleep disorders such as insomnia, hypersomnia, parasomnia, SDB (Sleep-disordered breathing), PLMS (Periodic Leg Movement during Sleep), and RLS (Restless Leg Syndrome) can worsen rehabilitation and increase the risk of recurrent strokes. The existing therapies are still in the research phase with varying prognoses, indicating the need for a deeper understanding of this condition and its management.